2018
DOI: 10.1016/j.jtbi.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sanctions on the evolution of cooperation in linear division of labor

Abstract: The evolution of cooperation is an unsolved research topic and has been investigated from the viewpoint of not only biology and other natural sciences but also social sciences. Much extant research has focused on the evolution of cooperation among peers. While, different players belonging to different organizations play different social roles, and players playing different social roles cooperate together to achieve their goals. We focus on the evolution of cooperation in linear division of labor that is define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In Nakamaru et al (2018) which made the concrete model fitting the industrial dumping system, the cost of cooperation decreases in the downstream roles. Nakamaru et al (2018) concluded that the first role sanction system promotes cooperation more than the defector sanction system especially when the probability of finding a defector is very low, which is also supported by our result when the cost of cooperation decreases in downstream groups. The difference between these two studies is that there are locally stable mixed equilibria such as (1 c , 2 c , 3 c ) = (1, 1, 0) in the baseline and two sanction systems in Nakamaru et al (2018), but in the defector sanction system when the cost of cooperation increases in downstream groups in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Nakamaru et al (2018) which made the concrete model fitting the industrial dumping system, the cost of cooperation decreases in the downstream roles. Nakamaru et al (2018) concluded that the first role sanction system promotes cooperation more than the defector sanction system especially when the probability of finding a defector is very low, which is also supported by our result when the cost of cooperation decreases in downstream groups. The difference between these two studies is that there are locally stable mixed equilibria such as (1 c , 2 c , 3 c ) = (1, 1, 0) in the baseline and two sanction systems in Nakamaru et al (2018), but in the defector sanction system when the cost of cooperation increases in downstream groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The player in the first role always gets punished for the defection, no matter which role defected. For example, this sanction system is executed to prevent illegal dumping in Japan (Nakamaru et al, 2018).…”
Section: The First Role Sanction Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear division of labor structure was adopted in accordance with the structure of industrial waste treatment in the Industrial Waste Illegal Dumping Game (Nakamaru, Shimura, Kitakaji, & Ohnuma, 2018). In linear division of labor, it is important to choose players for different roles, and the situation is highly interdependent among the players, depending on the associated negotiations, transactions, and/or reputations.…”
Section: Specificity Of the Industrial Waste Illegal Dumping Game Commentioning
confidence: 99%
“…These costs may inhibit the effect of monitoring and punishment. Therefore, monitoring and punishment are not always successful in illegal cases of commons, such as poaching, smuggling, illegal logging, and illegal dumping of industrial waste, all of which generally occur in secret and damage the natural environment (Jachmann 2003, Nakamaru et al 2018.…”
Section: Introductionmentioning
confidence: 99%